Ureteral atresia presenting as an abdominal cyst: A case report - Amir Ibrahim; Mohamed Mansy; Mostafa Kotb; Mohamed Abokandil; Saber Waheeb (Journal of Pediatric Surgery Case Reports, 2024)
Background: Ureteral atresia is a rare disease that is usually associated with a non-functioning dysplastic kidney. The condition may be unilateral or bilateral, short, or long, and may involve any part of the ureter. Case description: A 4-year-old boy presented with a gradually developing right-sided abdominal distension. Abdominal examination revealed a right lumbar mas of approximately 20 × 15 cm. Abdominal ultrasound showed a large cystic mass that extended from the hilum of the right kidney and crossed the midline to reach the left side of the abdomen. The left kidney was absent. Voiding cystourethrogram (VCUG) was unremarkable. Magnetic resonance urography (MRU) confirmed the presence of a thin-walled cystic lesion extending from the right renal hilum, crossing midline, reaching the left lumbar region, and the absence of the left kidney. Renal nuclear scan showed a functioning right kidney and an absent left kidney. Exploratory laparotomy via a Pfannenstiel incision revealed a normal right kidney and a large extraperitoneal abdominal cyst. This cyst contained about 200 cc of brownish fluid. The cystic mass was in fact a crossed fused left kidney with a proximal ureteral atresia. Excision of the cyst along with the left ureter was done. The postoperative course was uneventful. Conclusion: Ureteral atresia is a rare condition. It can result in a dysplastic kidney in the form of a large retroperitoneal abdominal cystic mass.